Web Based Claim Model for Bursar Department of Universiti Utara Malaysia - Yusra Asyikin, Md. Yunus (2009)
Manually claim process in current practice at UUM is time consuming,costly and very challenging. The claiming process involve a lot of activity,such as checking the eligibility condition that preserve in the claim guidelines books and verifying the application form with the supporting documents. The complexity of the manually claiming process causes the delay of the payment. Therefore, there is a need to develop a claim model that can contribute to the development of a web based claim system. The objectives of this study are to identify the requirements of the claiming process, to propose simplified model of claiming process and develop the web based claim prototype. The web based claim application is proposed to meet the business challenging in claiming process and allow the Bursar Department of UUM to work efficiently and effectively in order to satisfy their users especially the UUM staff.